Discredited Metaphors of Mind Limit Our Vision - Marilyn Middendorf (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Teachers will be intrigued by recent discoveries in "the brain sciences" and the new metaphors of consciousness they suggest.